The Art of Spiritual Care.: Implications for the use of instruments and tools - Boelsbjerg, Hanne Bess; Leget, Carlo (Tidsskrift for Forskning i Sygdom og Samfund, 2023)
The article defends the position that providing spiritual care first and foremost is an art in which tools and instruments are subordinate to practical knowledge, experience, and wisdom of the phenomenon. A growing number of instruments and tools for spiritual care have been developed, tested, and validated. Some have been designed for the purpose of doing research, others have been developed for the practice of spiritual caregiving. These instruments and tools have impact both on the way we provide spiritual care, and the way we look upon spiritual care. Behind these developments are different views about what counts as scientific knowledge, as the methodologies used are based in such different paradigms as natural sciences, social constructivism, and phenomenology. The methodology used impacts how spirituality and spiritual care are viewed, as a methodology shapes our understanding of the object which is studied. When viewing spiritual care as an art, we base this on an understanding of spiritual care as a dynamic and relational phenomenon. To support this perception, the article structures its arguments on the following elements: 1) The hermeneutic nature of spiritual caregiving 2) The role of the practice of spiritual caregiving 3) The nature of tacit and intuitive knowledge. The article bridges these arguments by providing empirical examples from spiritual care providers in Denmark.